2015
DOI: 10.1007/s40953-015-0009-0
|View full text |Cite
|
Sign up to set email alerts
|

The Level of Pollution and the Economic Growth Factor: A Nonparametric Approach to Environmental Kuznets Curve

Abstract: This paper uses nonparametric method to study the relationship between economic growth and the level of pollution. The results indicate that as income increases the level of PM10 pollution rises and falls for low-and middle-income countries, respectively. Countries with GDP per capita above $32,000 experience an increased pollution level. Statistical tests show that nonparametric result provides better analysis than cubic specification, which dominates research works. Among the control variables in semiparamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…By contrast, the eastern region exhibits no such correlation. Consistent with the EKC, this result implies that a high level of economic development may help to mitigate air pollution (Nigatu 2015;Hao and Liu 2016;Wang et al 2017;Luo et al 2018). In this case, economic development along with the continuing expansion of digital financial inclusion helps to reduce PM 2.5 concentration in the eastern region.…”
Section: Discussionsupporting
confidence: 63%
“…By contrast, the eastern region exhibits no such correlation. Consistent with the EKC, this result implies that a high level of economic development may help to mitigate air pollution (Nigatu 2015;Hao and Liu 2016;Wang et al 2017;Luo et al 2018). In this case, economic development along with the continuing expansion of digital financial inclusion helps to reduce PM 2.5 concentration in the eastern region.…”
Section: Discussionsupporting
confidence: 63%
“…Based on the extensive EKC literature, which has estimated CO 2 , SO 2 , and other industrial hazards discharge per unit output at the national level, 5 , 31 , 52 , 53 this study has focused on finding additional driving forces of the EKC, such as administrative ranking, and certifying whether the income level alters the relationship between hazardous discharge and economic growth. Although environmental disadvantages were found in developing countries, most studies omitted regional differences in identifying the sources of industrial pollution.…”
Section: Discussionmentioning
confidence: 99%
“…29 Similarly, Nigatu (2015) found that emissions from industrial hazardous PM10 have fallen in middle-income countries but have risen in low-income countries. 5 Obviously, there would be an inverted U-shape of pollution and economic growth in modernisation, whereas countries and economic zones that have a strong intention to maintain a high output might leave environmental protection behind. The above studies concluded that income-pollution relationships could be vague in countries that prioritise production expansion; hence, the EKC hypothesis does not always hold.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations